(untitled) (Research, Society and Development, 2020)
Technological advances in neonatology have contributed a lot to the reduction of infant mortality, mainly of premature extremes. According to data from the World Health Organization, 20 million premature babies are born worldwide every year, and of these, more than a third do not survive. In the last decades, several countries have adopted the Kangaroo Mother Method as a perinatal care strategy, with the intention of humanization within the Neonatal Intensive Care Units. This article aims to carry out a historical study of the origins until the implantation in Brazil of the Kangaroo Mother Method and reflect on the use of this therapy. This is a descriptive study, with a qualitative approach, in the reflexive modality. Although the method appeared at the end of the 1970s, its practice is still not fully disseminated, even though there is evidence of low cost, high benefit and resolution in hospitals that have implemented this type of assistance. With that, we conclude that it is extremely important to popularize and bring more elements to enrich the knowledge of professionals in the area to continue guaranteeing the success of the kangaroo mother method.